An Easy, General and Practical Method for the Construction of Alkyl Sulfonyl Fluorides. Issue 16 (9th July 2020) - Zhang, Xu; Fang, Wan‐Yin; Lekkala, Ravindar; Tang, Wenjian; Qin, Hua‐Li
Abstract: A visible light‐induced reductive addition of 1°, 2° and 3° alkyl iodides to ethenesulfonyl fluoride, employing Hantzsch ester as a hydrogen source at room temperature was developed. This method featured a wide substrate scope and great functional group compatibility, providing facile and robust process to alkyl sulfonyl fluorides including enzyme inhibitors, natural products and drugs derivatives in up to 99% yield. Further derivatization of resultant aliphatic sulfonyl fluorides was also achieved through sulfur fluoride exchange (SuFEx) reactions to deliver sulfonates and sulfonamides as privileged motifs for medicinal chemistry. Abstract :